THE STUDENTS’ ABILITY IN SPEAKING ACCURACY AND FLUENCY AT SMA NEGERI 9 GOWA - Andi Atika Putri; Nurdevi Bte Abdul; Sujariati (Journal of Language Testing and Assessment, 2021)
The purpose of this research aimed at finding out the students’ ability in speaking accuracy and fluency at SMA Negeri 9 Gowa class X IIS 1. The research used a descriptive quantitative method. The subject of this research was students in SMA Negeri 9 Gowa in tenth grade. The data of the research was collected through speaking tests in oral test form. The result of the research for speaking accuracy showed from 24 students’ there was 1 student (4.17%) who belonged to ‘excellent’ category, 4 students (16.67%) who belonged to ‘good’ category, 6 students (25%) who belonged to ‘fairly good’ category, 6 students (25%) who belonged to ‘poor’ category and 7 students (29.17%) who belonged to ‘very poor’ category. The mean score for speaking accuracy for students in SMA Negeri 9 Gowa at tenth grade was 5.6 which means the level of speaking accuracy of students was categorized as fair level. While for speaking fluency, the result of the research showed from 24 students’ there was 1 student (4.17%) who belonged to ‘excellent’ category, 4 students (16.67%) who belonged to ‘good’ category, 8 students (33.33%) who belonged to ‘fairly good’ category, 5 students (20.83%) who belonged to ‘poor’ category and 6 students (25%) who belonged to ‘very poor’ category. The mean score of speaking fluency of students in SMA Negeri 9 Gowa at tenth grade was 5.9 which mean it was categorized as fair level.